2016
DOI: 10.1073/pnas.1521727113
|View full text |Cite
|
Sign up to set email alerts
|

Physical and situational inequality on airplanes predicts air rage

Abstract: We posit that the modern airplane is a social microcosm of classbased society, and that the increasing incidence of "air rage" can be understood through the lens of inequality. Research on inequality typically examines the effects of relatively fixed, macrostructural forms of inequality, such as socioeconomic status; we examine how temporary exposure to both physical and situational inequality, induced by the design of environments, can foster antisocial behavior. We use a complete set of all onboard air rage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…In addition, Kuziemko and colleagues (2015) show that reminding respondents of increases in inequality shifts preferences toward increased taxation of the wealthy. Finally, DeCelles and Norton (2016) demonstrate that simply being exposed to inequality-walking through the first-class cabin of an airplane while boarding-can lead passengers seated in economy class to experience greater anger than if they are not exposed to first class, while Kuziemko et al (2014) demonstrates that even the temporary feeling of being in "last place" can affect redistributive preferences.…”
Section: Perceptions Of Inequality Shape Preferences For Redistributionmentioning
confidence: 99%
“…In addition, Kuziemko and colleagues (2015) show that reminding respondents of increases in inequality shifts preferences toward increased taxation of the wealthy. Finally, DeCelles and Norton (2016) demonstrate that simply being exposed to inequality-walking through the first-class cabin of an airplane while boarding-can lead passengers seated in economy class to experience greater anger than if they are not exposed to first class, while Kuziemko et al (2014) demonstrates that even the temporary feeling of being in "last place" can affect redistributive preferences.…”
Section: Perceptions Of Inequality Shape Preferences For Redistributionmentioning
confidence: 99%
“…In the United States, the gap between the top 1% of earners and everyone else was wider in 2012 than any time since before the Great Depression (1) and is a pervasive social and political phenomenon (2). With this phenomenon comes visible manifestations of inequality, which affect social interactions from cooperation (3) to conflict (4). However, very little is known about how direct exposure to inequality in everyday settings-such as poverty and homelessness in relatively wealthy neighborhoods-shapes human behavior.…”
mentioning
confidence: 99%
“…A handful of studies have examined the effect of context or subtle environmental cues on behavior (4,8) and attitudes (9). Although none of these studies has randomized encounters with real-world inequality, several recent studies examine the effect of perceptions of inequality on survey responses and laboratory behaviors (3,10,11).…”
mentioning
confidence: 99%
“…Subjective feelings of being disadvantaged in turn appear to be associated with interpersonal hostility and violent crime. In fact, several findings showed that the experience of personal relative deprivation is related to antisocial conduct and criminal outcomes (e.g., Baron, 2003;DeCelles & Norton, 2016;Mishra & Novakowski, 2016). Experimental evidence suggests that personal relative deprivation causally increases aggressive behaviour and related affect (Greitemeyer & Sagioglou, 2017).…”
mentioning
confidence: 99%